Picosecond resonance Raman evidence of the structure of a long-lived electronic excited state of low-spin Fe(III)heme o - Schelvis, Johannes P.M.; Varotsis, Constantinos (My University, 2000)
The structure of the excited state of low-spin ferric heme o has been studied using picosecond time-resolved resonance Raman spectroscopy. The excited state has a lifetime of 10–30 ps, and the heme skeletal vibrations are shifted to lower frequencies relative to those in the electronic ground state. Based on the relatively small frequency shifts, we conclude that the relatively long-lived heme o excited state is not a porphyrin ππ* state. We propose that the heme o excited state is a charge transfer state, in which the heme iron donates an electron to the porphyrin macrocycle.
Keywords: Pi-cation radicals; Triplet-state; Iron porphyrin; Spectra; Octaethylporphyrin; Spectroscopy; Transient; Zinc(II); Proteins; Tetraphenylporphyrin